AN ANALYSIS OF STUDENTS’ SPEAKING ANXIETY AT SMP AL-FALAH JAMBI - Susilawati, Susilawati; Alfian, Alfian; Tartila, Tartila (STKIP Siliwangi, 2025)
The aim of this research is to investigate the levels of speaking anxiety among students, the differences in speaking anxiety between male and female students, and the factors contributing to students’ speaking anxiety. The researcher used mixed method and SPSS program to analyzed the data kuantitative. Data were collected using the Foreign Language Classroom Anxiety Scale (FLCAS) by Horwitz, which consists of 33 positive and negative items. The results showed that 1.9% of students were very anxious, 25% were anxious, 59.6% were mildly anxious, and 13.5% felt relaxed during speaking activities. Although there was no significant difference in overall anxiety levels between male and female students, significant differences emerged when specific domains such as communication apprehension, test anxiety, and fear of negative evaluation were analyzed. In addition, the factors cause of students speaking anxiety; Communication Apprehension (CA), Test Anxiety, and Fear of Negative Evaluation (FNE).